Satisfied [videorecording (Blu-Ray)] - Goldsberry, Renée Elise, 1971-; Miranda, Lin-Manuel, 1980-; DeBose, Ariana, 1991- (Decal, 2025)
Amid the whirlwind of Hamilton's historic rise, Tony winner Renee Elise Goldsberry battles exhaustion, expectations, and the everyday chaos of motherhood. This revealing documentary pulls back the curtain on her pivotal role in the Broadway revolution and the personal cost of making history.